OVERVIEW OF SELF REGULATED LEARNING IN PANDEMI TIME IN AKADEMI KEPERAWATAN KESDAM ISKANDAR MUDA BANDA ACEH STUDENTS - Junizar; Adinda Amalia Zahra Lubis; Khairil Fauzan (RADJA PUBLIKA, 2023)
During the pandemic, students were forced to do online or online learning in accordance with government recommendations. The purpose of this study was to find out the description of self-regulating learning in students while studying online during the Covid 19 pandemic. This research is a quantitative research. Data collection tools in this study used a self-efficacy scale, parental support scale and self-regulating learning scale. This study used quantitative descriptive. There were 151 subjects in this research. The researcher conducted a T test with an alpha value of 0.05 and looked for a Z score from all the data obtained. The results of this study are that of a total of 151 subjects, there is high self-regulated learning in 55 female students, 6% while the male students were 44.4%. It can be concluded that the Iskandar Muda Kesdam Nursing Academy students have high self-regulated learning.